High-CTI insulating material and cable

By using LiCl modified nylon, (2,3-epoxypropyl)benzene and hydrated inorganic filler in cable insulation materials, the problem of insufficient leakage resistance and traceability performance in humid environments is solved, and higher leakage resistance and traceability performance and service life are achieved.

CN119899472APending Publication Date: 2025-04-29RUIXIN GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510085450.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing cable insulation materials have insufficient leakage resistance and traceability in wet or multi-liquid contaminated environments, which affects service life.

Method used

The coordinated addition of LiCl modified nylon and (2,3-epoxypropyl)benzene is adopted, and the addition of hydrated inorganic filler is added to improve the leakage resistance and traceability of the insulating material.

Benefits of technology

It significantly improves the leakage resistance and traceability of the insulating material, ensures that the cable works stably, safely and long-term in humid environments, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250001680000081
    Figure BDA0005250001680000081
  • Figure BDA0005250001680000091
    Figure BDA0005250001680000091
Patent Text Reader

Abstract

The invention discloses a high-CTI insulating material and a cable, the high-CTI insulating material comprises the following raw materials in parts by mass: 80-93 parts of polyvinyl chloride, 10-30 parts of LiCl modified nylon, and 4.6-8.3 parts of (2, 3-epoxypropyl) benzene, on the basis that nylon is added into polyvinyl chloride for modification, the LiCl modified nylon and (2, 3-epoxypropyl) benzene are cooperatively added, so that the mechanical property of the cable is improved, and the mechanical property of the cable is improved. The anti-creepage tracking performance of the insulating material can be remarkably improved, so that the cable has excellent anti-creepage tracking performance, can stably and safely work for a long time in a humid environment or an environment prone to liquid leakage, and is long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to power transmission, and more particularly to an insulation material and a cable with a high CTI. Background Art

[0002] Humid or liquid-polluted environments, such as chemical plants, power plants, coastal cities, and tropical areas, etc. These environments usually have higher requirements for cable insulation materials, so cables with higher CTI values ​​are needed to ensure safety and reliability.

[0003] The insulation materials of existing cables have been modified by adding nylon to polyvinyl chloride. Nylon not only has excellent physical and chemical properties, but also has unique gas production and arc blowing functions. When the insulating material is damaged and leaks, nylon reacts and decomposes rapidly under the leakage arc, releasing a large amount of gas. These gases diffuse rapidly to form a high-voltage area, which repels the ionized ions and cuts off the current, causing the arc to extinguish quickly. In addition, the gas produced by the decomposition of nylon blows away the carbon layer formed by carbonization on the surface of the material due to the leakage arc, which plays a role in removing carbon on the surface of the substrate, increasing the surface breakdown voltage, and suppressing leakage.

[0004] The applicant is optimistic about the prospect of tracking resistance of insulating materials modified by adding nylon to polyvinyl chloride. Further research and analysis found that since nylon is a crystalline type with more crystalline regions, adding nylon to polyvinyl chloride will increase the crystalline region in the insulating material, which is not conducive to the tracking resistance performance. Therefore, there is still room for further improvement in the tracking resistance performance of nylon-modified polyvinyl chloride insulating materials. Summary of the invention

[0005] In order to further improve the service life of the cable in a humid or liquid-polluted environment, a high CTI insulation material and cable are provided.

[0006] The above first invention objective of the present invention is achieved through the following technical solutions: A high CTI insulating material comprises the following raw materials in parts by weight: 80-93 parts of polyvinyl chloride; 10-30 parts of LiCl modified nylon; 4.6 to 8.3 parts of (2,3-epoxypropyl)benzene.

[0007] By adopting the above technical solution, nylon is modified by using LiCl, which not only reduces the nylon crystallization area and improves the voltage breakdown resistance of nylon, but also improves the mechanical properties of nylon; In addition, the modification mechanism of LiCl on nylon is that LiCl is added to form a complex with the oxygen atoms on the carbonyl group in nylon, destroying the hydrogen bond structure between nylon molecules and forming a more entangled structure, so that the movement of the chain segments in the composite material is restricted and relaxation is difficult, which makes it difficult for nylon to enter the crystal lattice during crystallization and restricts the crystallization behavior. When reducing crystallinity and improving mechanical properties, the hydrogen bond structure is destroyed, releasing more free NH, which enhances the water absorption of nylon and reduces the gain brought by the reduction of crystallinity of LiCl-modified nylon in tracking resistance. In this regard, (2,3-epoxypropyl)benzene is also added in this application. The amount of (2,3-epoxypropyl)benzene is greater than that of free NH, so that NH is reacted with (2,3-epoxypropyl)benzene as much as possible, reducing free NH. At the same time, due to the benzene ring of (2,3-epoxypropyl)benzene, the waterproofness of the insulating material is improved. Thus, (2,3-epoxypropyl)benzene reduces the defects of LiCl nylon action and further improves the water resistance of the insulating material, which is beneficial to improving the tracking resistance of the insulating material. In summary, the present application selects the synergistic addition of LiCl-modified nylon and (2,3-epoxypropyl)benzene on the basis of adding modified polyvinyl chloride to nylon, which can significantly improve the tracking resistance of the insulating material.

[0008] Optionally, the LiCl-modified nylon material is obtained by blending and modifying nylon 6, nylon 66 and LiCl.

[0009] By adopting the above technical scheme, the temperature resistance and organic solvent solubility resistance of nylon 6 are better than those of nylon 66, but its water absorption rate is higher than that of nylon 66. The combination of the two can coordinate the advantages of both, so that the strength and tracking resistance of the insulating material can be better.

[0010] Optional: Nylon 6, Nylon 66, LiCl mass ratio is 35:65:3.4.

[0011] By adopting the above technical solution, the strength, flame retardancy and tracking resistance of the insulating material are better.

[0012] Optionally, 20 to 31 parts of hydrated inorganic filler are also included.

[0013] By adopting the above technical solution, the organic flame retardant promotes the formation of a carbon layer on the surface of the material to isolate oxygen and achieve flame retardancy. The dense carbon layer makes the surface of the insulating material more susceptible to short circuit or arcing. The flame retardant mechanism of the organic flame retardant makes it unfavorable for the tracking resistance of the insulating material. Hydrated inorganic fillers will release water vapor at high temperatures to cool the material and isolate oxygen with water vapor. Their flame retardant mechanism will not weaken the insulation material's resistance to leakage tracking. It can also help remove carbon particles on the material surface during leakage tracking, reduce the decomposition of polymer insulation materials and the rate of carbon formation, and thus improve the insulation material's resistance to leakage tracking.

[0014] Optional: The hydrated inorganic filler is hydromagnesite powder.

[0015] By adopting the above technical solution, when the temperature of hydromagnesite is raised to 340°C, all the crystal water of hydromagnesite is lost and part of the structural water begins to be lost; when the temperature is raised to 477°C, all the structural water of hydromagnesite is released and hydromagnesite begins to decompose and lose part of the carbon dioxide; when the temperature is raised to 727°C, all the hydromagnesite is completely decomposed. Therefore, hydromagnesite powder can not only release water vapor at high temperature but also release carbon dioxide at further high temperature, and its flame retardant properties and the effect of improving the resistance to leakage tracking performance are better.

[0016] Optional: The surface of the hydrated inorganic filler is treated with a silane coupling agent.

[0017] By adopting the above technical solution, the compatibility of hydrated inorganic fillers in organic materials is improved, and the tracking resistance of insulating materials is improved.

[0018] Optional: The silane coupling agent is γ-glycidoxypropyltrimethoxysilane.

[0019] By adopting the above technical scheme, the compatibility of the hydrated inorganic filler modified by the general alkylsiloxane coupling agent with polyvinyl chloride is not ideal. The modified hydrated inorganic filler is modified by using γ-glycidoxypropyltrimethoxysilane. The modified hydrated inorganic filler not only has a wide range of improved compatibility with organic materials, but also can react with the residual NH on the molecular chain of the nylon material, thereby improving the compatibility and bonding strength of the hydrated inorganic filler with the organic material in the insulating material of the present application, thereby improving the tensile strength and tracking resistance of the insulating material.

[0020] The above second invention object of the present invention is achieved through the following technical solutions: A tracking-resistant cable is characterized in that it comprises a core and an insulating layer, wherein the insulating layer is made of the above-mentioned high CTI insulating material.

[0021] By adopting the above technical solution, the cable of the present application has excellent resistance to leakage tracking, can work stably, safely and for a long time in a humid environment or an environment prone to leakage, and has a long service life.

[0022] In summary, this application has at least the following beneficial effects: 1. Based on the modification of polyvinyl chloride by adding nylon, the present application selects the synergistic addition of LiCl-modified nylon and (2,3-epoxypropyl)benzene, which can significantly improve the tracking resistance of the insulating material; 2. Hydrated inorganic fillers are also added, which not only improves the flame retardancy and tensile strength of the insulating material, but also further improves the tracking resistance of the insulating material; 3. The cable of the present application has excellent resistance to leakage tracking, can work stably, safely and effectively in a humid environment or an environment prone to leakage, and has a long service life. DETAILED DESCRIPTION

[0023] raw material: Nylon 6 (PA6) is Japan Ube 1013B; Nylon 66 (PA66) is Japan Ube 2020B; LiCl was anhydrous LiCl powder, analytical grade; Hydromagnesite powder, composed of hydrated basic magnesium carbonate, is obtained by sieving commercially available hydromagnesite powder, with a particle size of 0.1 μm; Aluminum hydroxide, obtained by sieving commercially available aluminum hydroxide, with a particle size of 0.1 μm; γ-(2,3-glycidoxy)propyltrimethoxysilane, CAS: 2530-83-8, also known as 3-glycidoxypropyltrimethoxysilane, is a commercially available product of Nanjing Rongan Chemical Technology Co., Ltd.; Dimethyldimethoxysilane, CAS No.: 1112-39-6, is a commercial product of Nanjing Rongan Chemical Technology Co., Ltd.; (2,3-Epoxypropyl)benzene is a commercially available product of Shandong Yuchang Pharmaceutical Co., Ltd.

[0024] Preparation Example 1 LiCl modified nylon, the preparation method thereof is as follows: Anhydrous LiCl powder was sieved to obtain powder with a particle size of less than 10 μm, and the powder was dried in a drying oven at 100° C. for 10 h to obtain LiCl powder; PA6 and PA66 were dried in a drying oven at 80° C. for 12 h to obtain PA6 material and PA66 material; PA6 material, PA66 material and LiCl material were mixed evenly in a mass ratio of 35:65:3.4, put into a screw extruder for heating, extrusion and granulation to obtain homogeneous LiCl modified nylon; the melting section of the screw extruder was stabilized at 235°C.

[0025] Preparation Example 2 LiCl modified nylon, the preparation method thereof is as follows: Anhydrous LiCl powder was sieved to obtain powder with a particle size of less than 10 μm, and the powder was dried in a drying oven at 100° C. for 10 h to obtain LiCl powder; PA6 was dried in a drying oven at 80° C. for 12 h to obtain PA6 material; The PA6 material and the LiCl material were mixed evenly in a mass ratio of 100:3.4, and put into a screw extruder for heating, extrusion and granulation to obtain a homogeneous LiCl-modified nylon; the melting section of the screw extruder was stabilized at 235°C.

[0026] Preparation Example 3 LiCl modified nylon, the preparation method thereof is as follows: Anhydrous LiCl powder was sieved to obtain powder with a particle size of less than 10 μm, and the powder was dried in a drying oven at 100° C. for 10 h to obtain LiCl powder; PA66 was dried in a drying oven at 80° C. for 12 h to obtain PA66 material; The PA66 material and the LiCl material were mixed evenly in a mass ratio of 100:3.4, and put into a screw extruder for heating, extrusion and granulation to obtain a homogeneous LiCl modified nylon; the temperature of the melting section of the screw extruder was 225°C.

[0027] Preparation Example 4 A hydrated inorganic filler is obtained by modifying hydromagnesite, and the specific preparation method is as follows: Hydromagnesite powder and γ-glycidoxypropyltrimethoxysilane are put into a stirrer at a mass ratio of 100:6.7, and stirred at 35° C. and 120 r / min for 1 hour to obtain the product.

[0028] Preparation Example 5 A hydrated inorganic filler is obtained by modifying hydromagnesite, and the specific preparation method is as follows: Aluminum hydroxide powder and γ-glycidoxypropyltrimethoxysilane are put into a stirrer at a mass ratio of 100:6.7, and stirred at 35° C. and 120 r / min for 1 hour to obtain the product.

[0029] Preparation Example 6 A hydrated inorganic filler, which is hydromagnesite powder.

[0030] Preparation Example 7 A hydrated inorganic filler is obtained by modifying hydromagnesite, and the specific preparation method is as follows: Aluminum hydroxide powder and dimethyldimethoxysilane are put into a stirrer at a mass ratio of 100:6.7, and stirred at 35° C. and 120 r / min for 1 hour to obtain the product.

[0031] Preparation Example 8 A nylon material is obtained by blending PA6 and PA66, and the specific preparation method is as follows: The PA6 and PA66 were dried in a drying oven at 80°C for 12 hours to obtain PA6 and PA66 materials; The PA6 material and the PA66 material were uniformly mixed in a mass ratio of 35:65, and put into a screw extruder for heating, extrusion and granulation to obtain a nylon material; the melting section of the screw extruder was stabilized at 235°C.

[0032] Example 1 A high CTI insulating material is made of polyvinyl chloride, LiCl-modified nylon, (2,3-epoxypropyl)benzene and hydrated inorganic filler.

[0033] The LiCl-modified nylon was prepared in Preparation Example 1. The hydrated inorganic filler was prepared in Preparation Example 4.

[0034] The preparation method of high CTI insulation material is as follows: Polyvinyl chloride, LiCl-modified nylon, (2,3-epoxypropyl)benzene and hydrated inorganic filler were uniformly mixed in a mass ratio of 90:20:6.5:27, and sent to a screw extruder for melt extrusion and granulation to obtain a high CTI insulating material. The temperature of the melting section of the screw extruder was 205°C.

[0035] Comparative Example 1 An insulating material takes polyvinyl chloride, nylon and hydrated inorganic filler as raw materials.

[0036] The nylon was prepared in Preparation Example 8. The hydrated inorganic filler was prepared in Preparation Example 4.

[0037] The preparation method of the insulating material is as follows: Polyvinyl chloride, nylon and hydrated inorganic filler were uniformly mixed in a mass ratio of 90:20:27, and sent into a screw extruder for melt extrusion and granulation to obtain an insulating material. The temperature of the melting section of the screw extruder was 205°C.

[0038] Comparative Example 2 A high CTI insulating material is made of polyvinyl chloride, LiCl-modified nylon and hydrated inorganic filler.

[0039] The LiCl-modified nylon was prepared in Preparation Example 1. The hydrated inorganic filler was prepared in Preparation Example 4.

[0040] The preparation method of high CTI insulation material is as follows: Polyvinyl chloride, LiCl-modified nylon and hydrated inorganic filler were uniformly mixed in a mass ratio of 90:20:27, and sent to a screw extruder for melt extrusion and granulation to obtain a high CTI insulating material. The temperature of the screw extruder melting section was 205°C.

[0041] Comparative Example 3 A high CTI insulating material is made of polyvinyl chloride, (2,3-epoxypropyl)benzene and hydrated inorganic filler.

[0042] The hydrated inorganic filler is prepared in Preparation Example 4.

[0043] The preparation method of high CTI insulation material is as follows: Polyvinyl chloride, (2,3-epoxypropyl)benzene and hydrated inorganic filler were uniformly mixed in a mass ratio of 90:7.5:27, and sent to a screw extruder for melt extrusion and granulation to obtain a high CTI insulating material. The temperature of the melting section of the screw extruder was 205°C.

[0044] Comparative Example 4 An insulating material, which differs from Comparative Example 2 in that the mass ratio of polyvinyl chloride, LiCl-modified nylon and hydrated inorganic filler is 90:10:27.

[0045] Comparative Example 5 An insulating material, which differs from Comparative Example 2 in that the mass ratio of polyvinyl chloride, LiCl-modified nylon and hydrated inorganic filler is 90:30:27.

[0046] Example 2 An insulating material, which differs from Example 1 in that the mass ratio of polyvinyl chloride, LiCl-modified nylon, (2,3-epoxypropyl)benzene and hydrated inorganic filler is 90:10:4.6:27.

[0047] Example 3 An insulating material, which is different from Example 1 in that the mass ratio of polyvinyl chloride, LiCl-modified nylon, (2,3-epoxypropyl)benzene and hydrated inorganic filler is 90:30:8.3:27.

[0048] The materials of Examples 1 to 3 and Comparative Examples 1 to 5 were tested for CTI, flame retardancy, and tensile strength.

[0049] CTI: Tested according to GB42074-2022 Test method for determination of tracking resistance index and comparative tracking index of solid insulating materials.

[0050] Flame retardant grade: tested according to the test method specified in GB / T19666-2019.

[0051] Tensile strength: tested according to the test method specified in ISO9001-2015.

[0052] The test results are shown in the following table.

[0053] Table 1. Test results of Examples 1 to 3 and Comparative Examples 1 to 5 CTI / V Flame retardant grade Tensile strength / MPa Example 1 550 V0 62.5 Comparative Example 1 300 v1 45.0 Comparative Example 2 375 v0 50.4 Comparative Example 3 275 v1 37.1 Comparative Example 4 325 v0 41.3 Comparative Example 5 400 v1 49.9 Example 2 500 v0 50.0 Example 3 600 v0 66.7 Comparison of Comparative Example 1 and Comparative Example 2 shows that the CTI of Comparative Example 2 is better than that of Comparative Example 1. This is because LiCl-modified nylon destroys the hydrogen bond structure between nylon molecules compared to nylon, forming a structure with a higher degree of entanglement, thereby restricting the movement of chain segments in the composite material, making it difficult for nylon to be arranged into the lattice during crystallization, limiting the crystallization behavior, and reducing the crystallinity, resulting in an increase in the breakdown voltage and an increase in the CTI. At the same time, the tensile strength of Comparative Example 2 is better than that of Comparative Example 1, because the structure with a higher degree of entanglement provides better mechanical properties.

[0054] By comparing Comparative Example 2 with Comparative Examples 4 to 5, it can be seen that the amount of LiCl-modified nylon in Comparative Example 4, Comparative Example 2, and Comparative Example 5 gradually increases, but the increase in CTI from Comparative Example 2 to Comparative Example 5 is significantly less than the change from Comparative Example 4 to Comparative Example 2. The flame retardant grade of Comparative Example 5 is reduced due to the increase in the amount of LiCl-modified nylon, and the tensile strength of Comparative Example 5 is also reduced due to the increase in the amount of LiCl-modified nylon rather than the decrease in Comparative Example 2. The reason is that when the hydrogen bond structure of LiCl is destroyed and the crystallinity of nylon is modified during the modification process, more free NH is released, making the free radical activity of LiCl-modified nylon stronger, the flame retardancy is reduced, and the water absorption is enhanced. Compared with Comparative Example 2, Comparative Example 5 is more likely to absorb water in the tracking resistance test and in a humid environment. Its excessive amount of nylon causes its water absorption to affect the conductivity of the insulating material, thereby affecting the tracking resistance of the insulating material, reducing the gain brought by the reduction in the crystallinity of LiCl-modified nylon.

[0055] By comparing Example 1 with Comparative Examples 1 to 3, it can be seen that Example 1 is further developed on the basis of polyvinyl chloride and LiCl-modified nylon, and (2,3-epoxypropyl)benzene is added. The amount of (2,3-epoxypropyl)benzene is greater than that of free NH, so that NH is reacted with (2,3-epoxypropyl)benzene as much as possible, thereby reducing free NH. At the same time, due to the benzene ring of (2,3-epoxypropyl)benzene, the waterproofness of the insulating material is improved. Thus, (2,3-epoxypropyl)benzene reduces the defects of LiCl nylon and further improves the water resistance of the insulating material, which is beneficial to improving the tracking resistance of the insulating material. Under the synergistic effect of LiCl-modified nylon and (2,3-epoxypropyl)benzene, the tracking resistance and tensile strength of Example 1 are significantly better than those of Comparative Examples 1 to 3, and the flame retardant grade is better than that of Comparative Example 1. In particular, the comparison with Comparative Example 3 verifies that the compound formula of a single (2,3-epoxypropyl)benzene and polyvinyl chloride not only fails to improve CTI, but also leads to a decrease in CTI, flame retardant properties, and tensile strength.

[0056] In combination with Examples 3 to 4 and Comparative Examples 4 to 5, Example 3 has significantly improved CTI and tensile strength compared with Comparative Example 4; Example 4 has not only significantly improved CTI and tensile strength compared with Comparative Example 5, but also improved flame retardant grade compared with Comparative Example 5; at the same time, the CTI improvement change between Example 3, Example 1, and Example 4 did not show the significant attenuation due to the increase in nylon dosage that appeared between Comparative Example 4, Comparative Example 2, and Comparative Example 5. Only the tensile strength improvement brought by LiCl-modified nylon is close to the threshold value under the current small proportion. Therefore, it can be further verified that the decrease in flame retardancy caused by NH under the action of (2,3-epoxypropyl)benzene and the limited CTI improvement caused by water absorption in Examples 1 to 3 of the present application are overcome.

[0057] In summary, the present application selects the synergistic addition of LiCl-modified nylon and (2,3-epoxypropyl)benzene on the basis of adding modified polyvinyl chloride to nylon, which can significantly improve the tracking resistance of the insulating material.

[0058] Example 4 An insulating material, which is different from Example 3 in that the LiCl-modified nylon is prepared by Preparation Example 2.

[0059] Example 5 An insulating material, which is different from Example 3 in that the LiCl-modified nylon is prepared by Preparation Example 3.

[0060] Example 6 A high CTI insulating material is made of polyvinyl chloride, LiCl-modified nylon and (2,3-epoxypropyl)benzene as raw materials.

[0061] The LiCl-modified nylon was prepared in Preparation Example 1.

[0062] The preparation method of high CTI insulation material is as follows: Polyvinyl chloride, LiCl-modified nylon and (2,3-epoxypropyl)benzene were uniformly mixed in a mass ratio of 90:30:8.3, and sent to a screw extruder for melt extrusion and granulation to obtain a high CTI insulating material. The temperature of the melting section of the screw extruder was 205°C.

[0063] Example 7 A high CTI insulating material, which is different from Example 3 in that the hydrated inorganic filler is prepared by Preparation Example 5.

[0064] Example 8 A high CTI insulating material, which is different from Example 3 in that the hydrated inorganic filler is prepared by Preparation Example 6.

[0065] Example 9 A high CTI insulating material, which is different from Example 3 in that the hydrated inorganic filler is prepared by Preparation Example 7.

[0066] Example 10 A high CTI insulating material, which differs from Example 3 in that the mass ratio of polyvinyl chloride, LiCl-modified nylon, (2,3-epoxypropyl)benzene and hydrated inorganic filler is 80:10:4.6:20.

[0067] Embodiment 11 An insulating material, which differs from Example 3 in that the mass ratio of polyvinyl chloride, LiCl-modified nylon, (2,3-epoxypropyl)benzene and hydrated inorganic filler is 93:30:8.3:31.

[0068] The insulating materials of Examples 4 to 11 were tested for CTI, flame retardancy, and tensile strength.

[0069] The test results are shown in the following table.

[0070] Table 2. Test results of insulation materials of Examples 4 to 11 Combining Table 1 and Table 2, comparing Example 3 with Examples 4-5, the types of nylon are different, and there are also differences in performance. The temperature resistance and organic solvent solubility resistance of nylon 6 are better than those of nylon 66, but its water absorption rate is higher than that of nylon 66. The nylon used in the LiCl-modified nylon of Example 1 is a blend of PA6 and PA66, which has the advantages of both. Therefore, the CTI and tensile strength of Example 1 are better than those of Examples 4-5.

[0071] By comparing Example 3 and Example 6, it can be seen that no hydrated inorganic filler is added in Example 6, and the flame retardant grade of Example 6 is lower than that of Example 1, and the CTI and tensile strength are also lowered. This is because the hydrated inorganic filler will release water vapor at high temperature, cool the material and isolate oxygen with water vapor. Its flame retardant mechanism will not weaken the insulation material's resistance to leakage tracking, and it can also help to remove carbon particles on the material surface during leakage tracking, reduce the decomposition of the polymer insulation material and the carbon formation rate, and thus improve the insulation material's resistance to leakage tracking.

[0072] By comparing Example 3 and Example 7, it can be seen that the CTI of Example 3 is better than that of Example 7. The hydromagnesite selected in Example 3 can release water vapor only at high temperature and can also release carbon dioxide at a further high temperature, and has a better effect on improving the tracking resistance.

[0073] By comparing Example 3 with Examples 8 to 9, it can be seen that in Example 3, the hydromagnesite is surface-modified using γ-glycidoxypropyltrimethoxysilane, and in Example 9, the hydromagnesite is surface-modified using dimethyldimethoxysilane. In Example 8, the hydromagnesite is not surface-modified. In the test results, the CTI of Example 3 is better than that of Example 9, and the CTI of Example 9 is better than that of Example 8. Therefore, in the organic phase embodiment based on polyvinyl chloride and LiCl-modified nylon, the modification of the hydrated inorganic filler by a silane coupling agent can improve its compatibility in the organic phase, and the effect of surface modification by γ-glycidoxypropyltrimethoxysilane is better.

[0074] In combination with Examples 1 to 3 and Examples 10 to 11, it can be seen that when the mass ratio of polyvinyl chloride, LiCl-modified nylon, (2,3-epoxypropyl)benzene, and hydrated inorganic filler in the insulating material of the present application is controlled to be (80 to 93): (10 to 30: (4.6 to 8.3): (20 to 31), they can all have excellent anti-tracking performance.

[0075] Example 12 A cable comprises one or more electric cores. Each electric core is coated with an insulating layer, and the insulating layer is made of an insulating material in any one of embodiments 1 to 11.

[0076] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.

Claims

1. A high CTI insulating material, characterized in that: Including the following raw materials by mass: 80-93 parts of polyvinyl chloride; LiCl modified nylon 10-30 parts; 4.6 to 8.3 parts of (2,3-epoxypropyl)benzene.

2. The high CTI insulating material according to claim 1, characterized in that: The LiCl-modified nylon material is obtained by blending and modifying nylon 6, nylon 66 and LiCl.

3. The high CTI insulating material according to claim 2, characterized in that: The mass ratio of nylon 6, nylon 66 and LiCl is 35:65:3.

4.

4. The high CTI insulating material according to claim 1, characterized in that: It also includes 20 to 31 parts of hydrated inorganic filler.

5. The high CTI insulating material according to claim 4, characterized in that: The hydrated inorganic filler is hydromagnesite powder.

6. The high CTI insulating material according to claim 4, characterized in that: The surface of the hydrated inorganic filler is treated with a silane coupling agent.

7. The high CTI insulating material according to claim 4, characterized in that: The silane coupling agent is γ-glycidoxypropyltrimethoxysilane.

8. A tracking-resistant cable, comprising a battery core and an insulating layer, wherein the insulating layer is made of the high CTI insulating material according to any one of claims 1 to 7.